Penentuan Penerima Beasiswa Bidikmisi dengan Metode Elimination and Choice Translating Reality (ELECTRE) (Studi Kasus Politeknik Negeri Samarinda - Anton Topadang; Farindika Metandi; Damar Nurcahyono (JSAI (Journal Scientific and Applied Informatics), 2024)
ELECTRE is one of the decision support system algorithms that is suitable for use, because this algorithm works by processing the weighted values of each criterion and scholarship recipient candidate and produces an absolute value that is easy to use. Elimination and Choice Translating Reality (ELECTRE) method. ELECTRE is used because it is in accordance with the concept of ranking based on alternatives and criteria that have been applied, the ELECTRE method can be used in conditions where alternatives that are less suitable for the criteria are eliminated and suitable alternatives can be generated. The output of this system is a report on the ranking results of scholarship recipient candidates from KMB who are more feasible. Based on the calculations carried out, there are two alternatives in the first rank, namely M4 and M8, with the highest score of 5, while the third rank is filled by M3 and M7 with a score of 4. In the last rank, there are three alternatives, namely M2, M5, and M9, which get the lowest score of 2. From the results obtained, the ELECTRE method can be used as one of the methods in determining the ranking of scholarship recipients. Meanwhile, based on the success of the method in the assessment, the ELECTRE method in producing the best alternative is around 22.22% of the total alternatives evaluated.